A study on the Development of Posttraumatic Stress Symptomology among motor vehicle accident survivors. - Elanga, Ika Klei Sheendy P.
This research was conducted to see the relationship among social support, appraisal, coping strategies, and symptoms of PTSD on motor vehicle accident survivors. Participants (n=147) answered several composite measures and key informants were interviewed. The frameworks used in the study were Anxious Apprehension Model and Ehlers and Clark?s Cognitive Model respectively. Results of the study showed that social support and appraisal were significantly related with PTSD symptoms. These relationships were partly predicted by the frameworks. It is recommended that social support and cognitive reframing techniques (i.e. psychosocial) for survivors are created at the local level to provide an avenue for Post-Accident Stress Management.